Penguatan Kapasitas Siswa SMK Melalui Workshop Pembangunan Jaringan Komputer - Hutabri, Ellbert; Fauzi, Rahmat; Pratiwi, Mariska Putri; Putri, Anggia Dasa (Prosiding, 2024)
Advances in information and communication technology (ICT) have become a key factor in the development of various sectors, including education, industry and government. One of the important components in ICT is computer networks, which are the backbone for delivering data, information and digital services. Computer networks enable devices such as computers, servers, and other devices to communicate with each other, share resources, and access information efficiently. Therefore, mastering knowledge and skills in designing, building and managing computer networks is very important for individuals who want to pursue a career in the field of information technology. However, in some vocational schools that have Computer and Network Engineering majors, there are still students who do not have networking skills that suit the needs of the world of work, so workshops need to be provided so that students can improve their abilities before entering the world of work. The workshop was given over two days using lecture, case study and direct practice methods. Students will be invited to actively participate in each workshop session, so that they can understand the concepts taught better and apply them in real situations. Before the workshop, students were given a pre-test to find out the extent of their knowledge about computer networks. The pre-test results showed that the class average was 72.8. However, there were still some students whose scores were still below 70. During the workshop activities, students were given basic networking material, network topology, simulations with Sisco packet tracer and direct practice in building computer networks. After that, students were given a post-test to determine students' understanding of computer networks. The post-test results showed an increase in students' ability to build networks with a class average score of 83.4